The answer is 9x^2-4=y because when you inverse an equation you reverse it.
Answer:
Side A is 4
Step-by-step explanation:
Solve for d:
(3 (a + x))/b = 2 d - 3 c
(3 (a + x))/b = 2 d - 3 c is equivalent to 2 d - 3 c = (3 (a + x))/b:
2 d - 3 c = (3 (a + x))/b
Add 3 c to both sides:
2 d = 3 c + (3 (a + x))/b
Divide both sides by 2:
Answer: d = (3 c)/2 + (3 (a + x))/(2 b)
-----------------------------
Solve for x:
(3 (a + x))/b = 2 d - 3 c
Multiply both sides by b/3:
a + x = (2 b d)/3 - b c
Subtract a from both sides:
Answer: x = (2 b d)/3 + (-a - b c)
____________________________
Solve for b:
(3 (a + x))/b = 2 d - 3 c
Take the reciprocal of both sides:
b/(3 (a + x)) = 1/(2 d - 3 c)
Multiply both sides by 3 (a + x):
Answer: b = (3 (a + x))/(2 d - 3 c)
Answer:
1/6 for the cube and 1/2 for the coin
it would be 4/6 or 2/3 both are the same
Step-by-step explanation: sorry if im wrong btw
Option 2.)
(Please correct me if I'm wrong)